Classical Arabic biography : the heirs of the prophets in the age of al-Maʼmūn - Cooperson, Michael (Cambridge studies in Islamic civilization., 2000)
In the first book-length study to explore the origins of classical Arabic biography, the author demonstrates how Muslim scholars used notions of heirship and transmission to document the activities of political, scholarly and religious communities. The author illustrates his argument by analysing four figures whose biographies exemplify a particular tradition.